The Chemical Evolution of Star-forming Galaxies over the Last 11 Billion Years - Zahid, H. Jabran (2013)
We calculate the stellar mass–metallicity relation at five epochs ranging to z ∼ 2.3. We quantify evolution in the shape of the mass–metallicity relation as a function of redshift; the mass–metallicity relation flattens at late times. There is an empirical upper limit to the gas-phase oxygen abundance in star-forming galaxies that is independent of redshift. From examination of the mass–metallicity relation and its observed scatter, we show that the flattening at late times is a consequence of evolution in the stellar mass where galaxies enrich to this empirical upper metallicity limit; there is also evolution in the fraction of galaxies at a fixed stellar mass that enrich to this limit. The stellar mass where metallicities begin to saturate is ∼0.7 dex smaller in the local universe than it is at z ∼ 0.8.